ประสบการณ์ผู้ติดยาเสพติด 4x100 ของวัยรุ่นในตำบลแห่งหนึ่งของจังหวัดกระบี่ - บุหลาด, สุไหวด๊า; บุญแสง, ทวัช; รองเมือง, ดาราวรรณ (Ganesha Journal, 2015)
การศึกษาเชิงปรากฏการณ์วิทยานี้ มีวัตถุประสงค์เพื่อบรรยายและอธิบายประสบการณ์ ของวัยรุ่นที่เคยเสพยาเสพติดประเภท 4x100 มานาน ไม่น้อยกว่า 1 ปี จำนวน 10 คน รวบรวมข้อมูลโดยการสัมภาษณ์เชิงลึกใช้วิธีการสัมภาษณ์แบบกึ่งโครงสร้าง (Semi-Structured Interview) ใช้การสังเกตแบบไม่มีส่วนร่วม (Nonparticipation Observation) ระยะเวลาในการศึกษา 6 เดือน วิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหา จากการศึกษาพบว่าวัยรุ่นมีประสบการณ์การเสพยาเสพติด 4x100 3 ด้าน คือ 1) การเข้าสู่กระบวนการเสพของวัยรุ่นที่ติดยาเสพติด 4x100 พบว่าส่วนใหญ่วัยรุ่นเสพยาเสพติดชนิดอื่นมาก่อนได้แก่ สูบบุหรี่ สูบใบจากยาเส้น ยาบ้าและยาไอซ์ สาเหตุการเสพยาเสพติด 4x100 ของวัยรุ่น มาจากเพื่อนชวนให้ลองเสพ 2) วัยรุ่นที่ติดยาเสพติด 4x100 มีการผลิตและการจัดหาส่วนผสม พบว่าวัยรุ่นนิยมใช้สูตรธรรมดาหรือสูตรทั่วไป ประกอบด้วย น้ำต้มใบกระท่อม ผสมยาแก้ไอ น้ำโค้ก ดื่มกับน้ำแข็ง มีการทดลองผสมสารตัวอื่นเช่น ยาแก้แพ้ ยาจุดกันยุง แต่ไม่ชอบรสชาติและกลิ่น กลัวอันตราย การจัดหาส่วนผสม โดยซื้อจากร้านค้าในหมู่บ้านและจากต่างหมู่บ้าน ต่างอำเภอและต่างวังหวัด และ 3) การรับรู้ประสิทธิภาพและผลเฉียบพลัน ทั้งด้านอาการ และความรู้สึก จากการดื่ม 4x100 ของวัยรุ่นที่ติดยาเสพติด 4x100 พบว่า ผลของการเสพด้านบวกได้แก่ พึงพอใจในรสชาด รู้สึกมึน เมา ทำให้สบายใจ สมองโล่งโปร่ง นอนหลับ กระปริกระเปรา ด้านลบจะพบในช่วงที่หยุดเสพ ได้แก่ รู้สึกอยากเสพ ฟุ้งซ่าน กระวนกระวายหงุดหงิด นอนไม่หลับ น้ำหนักลดลง ปวดเมื่อยตามตัว ตามกระดูก อ่อนเพลีย ไม่มีแรงทำงาน ผลการศึกษาพบว่าครอบครัวและสังคมรอบข้างรับรู้และยอมรับการติดยาของวัยแต่ไม่มีมาตรการใดๆหยุดยั้งวัยรุ่นที่ติดยาเสพติด 4X10 Experience of Addiction 4X100 of the Teenagers in La Sub district of Krabi Province This phenomenological study aimed to describe and explain the experience of teenagers who had been drug addicts from the drug named 4x100. Key informants are 10 teenagers who have been addicted to 4x100 at least 1 year. Data were obtained using in-depth interviews using semi-structured interviews and non-participant observation over a 6-month period. Data were analyzed using content analysis. The results revealed that teens described their drug experience of 4x100 in 3 domains. 1) Access to their process of drug addiction found that most of the teenagers used to smoke and use methamphetamine and they were invited by a friend to try the drug. 2) Manufacturing and supplying the ingredients - teenagers use a formula that include Kratom and boiled water mixed with cough syrup, Coke, and they drink it with ice. They also made an experiment by mixing Kratom with other ingredients such as antihistamines and mosquito coil. However, they did not like the taste and smell of it. Moreover, they fear that it is dangerous. They usually buy their ingredients from local stores in the village and from other province. 3) Perception of the effectiveness and acute effects include signs and symptoms from drinking 4x100.The positive effects include feeling of satisfaction, dizziness, drunk, consoled, open mind, good sleep, and fresh but when they try to quit drinking, the negative effects usually occur such as: urges to drink, nervousness, irritability, insomnia, weight loss, bone and body aches, fatigue, and weakness. Moreover, the impact of families and society around them showed interesting results that they all recognize and accept the teenage drug abuse behavior. But no measures to stop teenage drug abuse 4x100.